A new cognitive evaluation battery for Down syndrome and its relevance for clinical trials - de Sola, Susana; de la Torre, Rafael; Sánchez-Benavides, Gonzalo; Benejam, Bessy; Cuenca-Royo, Aida; del Hoyo, Laura; Rodríguez, Joan; Catuara-Solarz, Silvina; Sanchez-Gutierrez, Judit; Dueñas-Espin, Ivan; Hernandez, Gimena; Peña-Casanova, Jordi; et al. (Frontiers in Psychology, 2015)
The recent prospect of pharmaceutical interventions for cognitive impairment of Down syndrome(DS) has boosted a number of clinical trials in this population. However, running the trials has raised some methodological challenges and questioned the prevailing methodology used to evaluate cognitive functioning of DS individuals. This is usually achieved by comparing DS individuals to matched healthy controls of the same mental age. We propose a new tool, the TESDAD Battery that uses comparison with age-matched typically developed adults. This is an advantageous method for probing the clinical efficacy of DS therapies, allowing the interpretation and prediction of functional outcomes in clinical trials. In our DS population the TESDAD battery permitted a quantitative assessment of cognitive defects, which indicated language dysfunction and deficits in executive function, as the most important contributors to other cognitive and adaptive behavior outcomes as predictors of functional change in DS. Concretely, auditory comprehension and functional academics showed the highest potential as end-point measures of therapeutic intervention for clinical trials: the former as a cognitive key target for therapeutic intervention, and the latter as a primary functional outcome measure of clinical efficacy. Our results also emphasize the need to explore the modulating effects of IQ, gender and age on cognitive enhancing treatments. Noticeably, women performed significantly better than men of the same age and IQ in most cognitive tests, with the most consistent differences occurring in memory and executive functioning and negative trends rarely emerged on quality of life linked to the effect of age after adjusting for IQ and gender. In sum, the TESDAD battery is a useful neurocognitive tool for probing the clinical efficacy of experimental therapies in interventional studies in the DS population suggesting that age-matched controls are advantageous for determining normalization of DS.